Collision-adhesion mechanism of particles and dust deposition simulation on solar PV modules. (October 2021) - Zhao, Weiping; Lv, Yukun; Zhou, Qingwen; Yan, Weiping
Abstract: Dust accumulation has a significant influence on the performance of solar photovoltaic (PV) modules. Investigating the particle collision-adhesion mechanism helps to understand dust accumulation characteristics of PV modules and provide theoretical support for dust removal work, and hence, improve PV efficiency. This study established a collision-adhesion model between particles and PV modules. Then, the mechanical equilibrium-based and energy-based particle adhesion mechanisms were explored and particle deposition condition was proposed. Furthermore, a dust accumulation experiment was created to verify the rationality of simulation model, which was constructed using energy-based particle adhesion mechanism. Based on this, a simulation was performed on the impact of various factors on particle deposition. The results showed the particle kinetic energy loss with a magnitude of 10 −13 J in the collision was positively correlated with humidity and particle size, while negatively correlated with wind speed and tilt angle. The particle deposition amount first decreases and then increases with increasing wind speed and particle size. However, it increases with increasing humidity and decreases with increasing tilt angle. Additionally, when the tilt angle increases from 15° to 60°, the particle deposition amount reduced from 4.28 g/m 2 to 1.81 g/m 2 under 7 m/s. In the future construction of PV power plants, for the area where particle size and average annual wind speed are less than 30 μm and 7 m/s, increasing the tilt angle appropriately can reduce dust accumulation. Graphical abstract: Understanding the movement process and the force behavior of particles is the premise to investigate the particle adhesion mechanism and deposition conditions. Besides, the collision between the particle and PV panel is an essential precondition for the deposition of particles on the panel surface. Therefore, the collision-adhesion physical model between the particle and PV panel surface is established. In a humid environment, the panel surface will absorb a water film of certain thickness, and increasing humidity will increase the water film thickness. To facilitate the analysis, it can be equivalent to a water film with uniform thickness. When the particles integrated with the wind move to the PV panel surface and collide with it, they usually go through four stages: incident, collision deformation, deformation recovery, and reflection stage, as shown in Fig. A above.The unbalanced force is the main reason for the particle deposition on the PV module surface . Therefore, according to collision-adhesion physical model between the particle and PV panel surface, the particle force behavior in the collision-adhesion process is analyzed, as shown in Fig. B above. This lays a foundation for the investigation of particle adhesion mechanism and the proposal of deposition conditions in this paper. Image 1 Highlights: Particle deposition criterion condition is proposed. A collision-adhesion model between the particle and PV module is built. Particle adhesion mechanism based on mechanical equilibrium and energy is explored. A dust accumulation experiment is done to verify the simulation model rationality. Effect of various factors on particle deposition in humid condition is simulated.